2011
DOI: 10.1089/neu.2010.1555
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging of Incentive Effects in Prospective Memory after Pediatric Traumatic Brain Injury

Abstract: Few studies exist investigating the brain-behavior relations of event-based prospective memory (EB-PM) impairments following traumatic brain injury (TBI). To address this, children with moderate-to-severe TBI performed an EB-PM test with two motivational enhancement conditions and underwent concurrent diffusion tensor imaging (DTI) at 3 months post-injury. Children with orthopedic injuries (OI; n=37) or moderate-to-severe TBI (n=40) were contrasted. Significant group differences were found for fractional aniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 172 publications
(209 reference statements)
1
43
0
Order By: Relevance
“…Significant differences in the FA, ADC, or MD, or other DTIderived diffusivity metrics have been demonstrated in studies of TBI in both adults (Bigler et al, 2010b;Kraus et al, 2007;Lipton et al, 2008;Perlbarg et al, 2009;Warner et al, 2010a) and children (Ewing-Cobbs et al, 2008;Levin et al, 2008;McCauley et al, 2011;Wilde et al, 2006bWilde et al, , 2010Wozniak et al, 2007;Wu et al, 2010a;Yuan et al, 2007), with decreases in FA and increases in measures of diffusivity often found in chronic post-injury intervals. More importantly, changes in DTIderived measures have shown correlation with injury severity (Arfanakis et al, 2002;Benson et al, 2007;Wilde et al, 2010;Yuan et al, 2007), functional outcome (Huisman et al, 2004;Levin et al, 2008;Salmond et al, 2006;Wozniak et al, 2007), neurologic functioning (Caeyenberghs et al, 2010a,b), and cognitive ability (Bigler et al, 2010b;Ewing-Cobbs et al, 2008;Kraus et al, 2007;Kumar et al, 2009;Levin et al, 2008;McCauley et al, 2011;Niogi et al, 2008;Salmond et al, 2006;Warner et al, 2010a;Wilde et al, 2010). Longitudinal studies have also indicated that DTI might serve as a tool for revealing changes in the neural tissue during recovery from TBI (Bendlin et al, 2008;Sidaros et al, 2008;Wu et al, 2010a).…”
Section: Fig 1 Ct (A)mentioning
confidence: 99%
“…Significant differences in the FA, ADC, or MD, or other DTIderived diffusivity metrics have been demonstrated in studies of TBI in both adults (Bigler et al, 2010b;Kraus et al, 2007;Lipton et al, 2008;Perlbarg et al, 2009;Warner et al, 2010a) and children (Ewing-Cobbs et al, 2008;Levin et al, 2008;McCauley et al, 2011;Wilde et al, 2006bWilde et al, , 2010Wozniak et al, 2007;Wu et al, 2010a;Yuan et al, 2007), with decreases in FA and increases in measures of diffusivity often found in chronic post-injury intervals. More importantly, changes in DTIderived measures have shown correlation with injury severity (Arfanakis et al, 2002;Benson et al, 2007;Wilde et al, 2010;Yuan et al, 2007), functional outcome (Huisman et al, 2004;Levin et al, 2008;Salmond et al, 2006;Wozniak et al, 2007), neurologic functioning (Caeyenberghs et al, 2010a,b), and cognitive ability (Bigler et al, 2010b;Ewing-Cobbs et al, 2008;Kraus et al, 2007;Kumar et al, 2009;Levin et al, 2008;McCauley et al, 2011;Niogi et al, 2008;Salmond et al, 2006;Warner et al, 2010a;Wilde et al, 2010). Longitudinal studies have also indicated that DTI might serve as a tool for revealing changes in the neural tissue during recovery from TBI (Bendlin et al, 2008;Sidaros et al, 2008;Wu et al, 2010a).…”
Section: Fig 1 Ct (A)mentioning
confidence: 99%
“…5 Thus, the pathophysiology of pmTBI and the subsequent relationship to neurobehavioral sequelae remain actively debated. Diffusion tensor imaging (DTI) has emerged as a potential mechanism for non-invasively measuring traumatic injuries, with the majority of studies focusing on moderate-to-severe [6][7][8][9] or mixed 10,11 pediatric injury cohorts at more chronic (e.g., months to years post-injury) time-points. The majority of these studies report decreased fractional anisotropy (FA) in the white matter of chronic patients.…”
Section: Introductionmentioning
confidence: 99%
“…The main method to manipulate the importance of a prospective memory task is to promise a reward for successful prospective memory performance (e.g., Aberle, Rendell, Rose, McDaniel, & Kliegel, 2010;Guajardo & Best, 2000;Jeong & Cranney, 2009;Krishnan & Shapiro, 1999;McCauley et al, 2011;Meacham & Singer, 1977).…”
mentioning
confidence: 99%